The Trinitarian faith : the Evangelical theology of the ancient Catholic faith - Torrance, Thomas F. (Thomas Forsyth), 1913-2007 (Cornerstones (London, England), 2016)
"Cutting across the divide between East and West and between Catholic and Evangelical, Thomas F. Torrance illuminates our understanding of the doctrine of the Holy Trinity. Torrance combines here the Gospel and a theology shaped by Karl Barth and the Church Fathers, and offers his readers a unique synthesis fo the Nicene Creed."--Back cover.